Thermal Degradation of Polysiloxanes Containing Chloropropyl Groups. (September 2019) - Dong, Fuying; Li, Shuaijie; Wang, Chenxing; Zhang, Meng; Xie, Guoqiang
Abstract: We synthesized a series of polysiloxanes containing chloropropyl groups, and studied its thermal stability and degradation mechanism through thermogravimetric analysis (TGA) in nitrogen atmosphere. The effect of the introduced chloropropyl units on the thermal degradation behavior of polysiloxanes was discussed. The depolymerization of the main chain of polysiloxane was accelerated by increasing the molar content of chloropropyl groups. The introduction of chloropropyl groups can cause the formation of a cross-linking network in the residue of polysiloxanes at 800 °C and restrain the formation of volatile components.